ChemInform Abstract: Rapid Synthesis of Oligomannosides with Orthogonally Protected Monosaccharides. Issue 37 (22nd August 2013) - Chang, Sue‐Ming; Tu, Zhijay; Jan, Hau‐Ming; Pan, Jia‐Fu; Lin, Chun‐Hung
Abstract A consecutive synthetic procedure to synthesize orthogonally protected mannose building blocks is described.